2009
DOI: 10.1002/pola.23692
|View full text |Cite
|
Sign up to set email alerts
|

An environmentally benign room temperature aqueous homo‐ and copolymerization of styrene and methylmethacrylate catalyzed by [Cp2TiCl2]/NaBPh4

Abstract: [Cp2TiCl2] has been found to be an effective precatalyst for room temperature aqueous homo‐ and copolymerization of methyl methacrylate and styrene in the presence of a cocatalyst, NaBPh4 and an emulsifier, sodium n‐dodecyl sulfate. The polymers obtained are of high molecular weight with low molecular weight distribution. © 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 6496–6503, 2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…However, in the presence of NaBPh 4 it can easily copolymerize the monomers. The stereoselectivity of the present catalytic system in copolymerization reaction is much better as we could obtain copolymer containing up to 77% cosyndiospecific MMA units whereas no such stereoselectivity could be observed in case of [Cp 2 TiCl 2 ] + NaBPh 4 catalyzed copolymerization 12…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…However, in the presence of NaBPh 4 it can easily copolymerize the monomers. The stereoselectivity of the present catalytic system in copolymerization reaction is much better as we could obtain copolymer containing up to 77% cosyndiospecific MMA units whereas no such stereoselectivity could be observed in case of [Cp 2 TiCl 2 ] + NaBPh 4 catalyzed copolymerization 12…”
Section: Resultsmentioning
confidence: 79%
“…So in our earlier works we suggested that, a cationic species, [Cp 2 MOH] + (M = Ti or Zr) is the active catalyst and this cation is stabilized by sodium n ‐dodecyl sulfate anion 10, 11. Recently we have reported the effect of various large, soft and noncoordinating anions on the catalytic activity of Cp 2 TiCl 2 in aqueous medium 12. Similar studies have been done on Cp 2 ZrCl 2 in presence of various counter‐anions namely ClO 4 − , PF 6 − , BPh 4 − , BF 4 − , etc., and the results are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31] Organo-titanium (III) species, which are readily obtained by the reduction of inexpensive Cp 2 TiCl 2 with Zn, have been reported to catalyze styrene, substituted styrene or conjugated diene living radical polymerization initiated by epoxides, peroxides or aldehydes. [28][29][30][31] In the literature, a few articles by Bhattacharjee et al [32][33][34][35][36] have described the use of Cp 2 MCl 2 (with Cp ¼ cyclopentadienyl and M ¼ Ti, Zr) as an active catalytic precursor for the aqueous emulsion homopolymerization of styrene and methylmethacrylate. This Cp 2 MCl 2 -catalyzed reaction produced stereoirregular polymers that had high molecular weights.…”
Section: Introductionmentioning
confidence: 99%